A 2-Year Longitudinal Study of Myopia Progression and Optical Component Changes among Hong Kong Schoolchildren - SIU YIN LAM, CARLY; EDWARDS, MARION; MILLODOT, MICHEL; HAN GOH, WINNIE SHUK (Optometry and vision science, 1999)
This study investigated refractive error and optical component changes in a group of 142 Hong Kong schoolchildren from age 6 to 17 years over a 2-year period between 1991 and 1993. Subjects were refracted subjectively and corneal curvatures and ocular dimensions were measured. At the end of the 2-year study, the mean spherical equivalent refraction (SER) was -1.86 D (SD 1.99 D) and 62% of the schoolchildren were myopic. The annual incidence of myopia was 11.8%. Children aged 10 years and under had a greater change in SER toward myopia than older children. The annual rate of myopia progression for the myopic children was -0.46 D (SD 0.40 D) and the rate of progression was greatest between age 6 and 10 years old. Vitreous depth/axial length elongation was the main component contributing to the progression of myopia. Hong Kong schoolchildren develop myopia as early as 6 years old and myopia progresses at a greater rate compared with children of European extraction.